The Sum and Product of Independence Numbers of Graphs and their Line Graphs - C., Susanth; Kalayathankal, Sunny Joseph (Journal of Informatics and Mathematical Sciences, 2014)
The bounds on the sum and product of chromatic numbers of a graph and its complement are known as Nordhaus-Gaddum inequalities. In this paper, we study the bounds on the sum and product of the independence numbers of graphs and their line graphs. We also provide a new characterization of the certain graph classes.